2018
DOI: 10.1056/nejmoa1507598
|View full text |Cite
|
Sign up to set email alerts
|

Trial of Prazosin for Post-Traumatic Stress Disorder in Military Veterans

Abstract: In this trial involving military veterans who had chronic PTSD, prazosin did not alleviate distressing dreams or improve sleep quality. (Funded by the Department of Veterans Affairs Cooperative Studies Program; PACT ClinicalTrials.gov number, NCT00532493 .).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(210 citation statements)
references
References 30 publications
5
203
0
2
Order By: Relevance
“…The AASM recommended prazosin as an adjunct therapy for PTSD, including nightmares (Aurora et al., , on behalf of the AASM). However, there was a recent large‐scale multicentre trial that did not yield any improvements (Raskind et al., ) and another trial in which patients returned to their baseline levels after treatment was discontinued (Raskind et al., ). These conflicting data caused the AASM to downgrade their advice regarding prazosin from “recommended” to “may be used” and to name other pharmaceuticals that “may be used” as well (Morgenthaler et al., , on behalf of the AASM).…”
Section: The Treatment Of Nightmare Disordermentioning
confidence: 99%
“…The AASM recommended prazosin as an adjunct therapy for PTSD, including nightmares (Aurora et al., , on behalf of the AASM). However, there was a recent large‐scale multicentre trial that did not yield any improvements (Raskind et al., ) and another trial in which patients returned to their baseline levels after treatment was discontinued (Raskind et al., ). These conflicting data caused the AASM to downgrade their advice regarding prazosin from “recommended” to “may be used” and to name other pharmaceuticals that “may be used” as well (Morgenthaler et al., , on behalf of the AASM).…”
Section: The Treatment Of Nightmare Disordermentioning
confidence: 99%
“…Several RCTs with varying sample sizes of veterans and civilians demonstrate safety, tolerability and efficacy of prazosin to reduce nightmares, sleep impairment, and overall PTSD symptom severity [1,18,5153,59,68], as well as AUD severity [59,60]. However, the largest RCT to date examining prazosin in the treatment of PTSD ( N = 304) [49] resulted in null findings. Veterans in this study were recruited from 13 VA hospitals across the nation.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary for future studies to explore the possibility that some Veterans might benefit from initiating prazosin earlier in their course of treatment or sooner after PTSD onset. In the [49] study, approximately one third of participants with similar distributions between medication conditions received individual or group psychotherapy ( n = 43; 28%) and the majority of participants were prescribed antidepressants (95% and 89% in the prazosin vs. placebo group, respectively). Thus, an additional consideration posed by the authors is that prazosin is less efficacious in the context of an established course of evidence-supported medications and/or psychotherapy to treat PTSD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 However, a recent large multisite clinical trial in Veterans with PTSD and nightmare disorder showed no benefit of sleep symptoms with prazosin. 51 Clonazepam has also been tried. While clonazepam did improve sleep onset and maintenance insomnia symptoms in a pilot study of patients with combat-related PTSD, it did not improve nightmares associated with combat-related PTSD.…”
Section: Treatmentmentioning
confidence: 99%